The international protection of the embryo and fetus - Scalabrino Spadea, Michelangela (Medicina e Morale, 1989)
The Parliamentary Assembly of the Council of Europe recently returned to the issue of the legal protection of human embryos and fetuses. As twice before in the recent past, the collaboration of the Committees on Science and Technology, Social Problems, Health and Family, and Legal Affairs resulted in a recommendation, which stands as a further step in identifying the basic principles of the future domestic and international regulation of intrauterine life.